Introduction: Thematic Papers Issue on Peripheral Nerve Regeneration and Repair. Issue 10 (17th October 2018) - Navarro, Xavier; Geuna, Stefano; Grothe, Claudia; Haastert‐Talini, Kirsten
ABSTRACT: Injuries to the peripheral nerves result in loss of motor, sensory and autonomic functions in the denervated segments of the body, thus having strong impact in the quality of life of affected patients. Neurons are able to regenerate their injured axons in the peripheral nerves; however, the endogenous repair mechanisms usually do not allow for a satisfactory functional recovery, especially after severe nerve injuries. The interest on regeneration after peripheral nerve injuries has increased in the recent years due to the numerous advances derived from studies of neurobiology, cell therapy, and tissue engineering. This Thematic Papers Issue brings together a number of papers, authored by researchers in the field, which cover a wide spectrum of topics related to regeneration and repair of peripheral nerve injuries. The Issue proposal originated from the recent 4th International Symposium on Peripheral Nerve Regeneration (ISPNR2017) which was hosted by Xavier Navarro and the European Society for the Study of Peripheral Nerve Repair and Regeneration in Barcelona, Spain. Anat Rec, 301:1614–1617, 2018. © 2018 Wiley Periodicals, Inc.